Relationship of Epidermal Growth Factor (EGF) and Insulin-Like Growth Factor-1 (IGF-1) levels in breast milk colostrum with the occurrence of necrotizing enterocolitis in neonates - Anik Puryatni; Prasetya Ismail; Fireka Juniantika; Bayu Kurniawan (Medical Faculty of Brawijaya University, Indonesia, 2022)
Background: Colostrum contains various bioactive compounds that have various roles and potentials in preventing the occurrence of necrotizing enterocolitis (NEC). EGF and IGF-1 are growth factors found in breast milk colostrum in the form of polypeptides that play a role in regulating and stimulating cell proliferation and differentiation processes. The purpose of this study was to determine the relationship between EGF and IGF-1 levels in breast milk colostrum with the occurrence of NEC in neonates. Methods: This analytical observational study was conducted at Saiful Anwar Hospital Malang during June-August 2019 on mothers and neonates who were breastfed. Maternal colostrum was collected at 72 hours postpartum, while NEC incidence in infants was determined prospectively. EGF and IGF-1 levels in colostrum were examined using the ELISA method. The data were processed by SPSS 21 program and analyzed using Spearman’s test and logistic regression. Results: 24 mother and baby pair samples were included in the study. The mean level of EGF in maternal colostrum was 466±304 ng/ml, and the mean level of IGF-1 was 1.99±0.96 ng/ml with no significant difference in levels based on gestational age. There is a strong negative correlation between the levels of EGF (r = -0.630; p=0.001) and IGF-1 (r = -0.646; p=0.001) on the occurrence of NEC. With the regression test, there was no significant effect between the levels of IGF-1 (p=0.995) and EGF (p=0.997) on NEC occurrence. Conclusion: EGF and IGF-1 levels have a significant relationship to the occurrence of NEC. The higher levels of EGF and IGF-1 contained in breast milk colostrum reduced the incidence of necrotizing enterocolitis in neonates.